Sheep 101 - Morris, Richard T., 1969-; Pham, LeUyen (New York ; Boston : Little, Brown and Company, 2018)
100 sheep have leapt over a fence to help a child fall asleep, but when the 101st sheep gets stuck, chaos ensues.
Keywords: Sheep -- Fiction; Bedtime -- Fiction; Humorous stories